2007
DOI: 10.1109/robot.2007.363619
|View full text |Cite
|
Sign up to set email alerts
|

Flying Fast and Low Among Obstacles

Abstract: Abstract-Safe autonomous flight is essential for widespread acceptance of aircraft that must fly close to the ground. We have developed a method of collision avoidance that can be used in three dimensions in much the same way as autonomous ground vehicles that navigate over unexplored terrain. Safe navigation is accomplished by a combination of online environmental sensing, path planning and collision avoidance. Here we report results with an autonomous helicopter that operates at low elevations in uncharted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…Suzuki et al used A* based approach for waypoint generation and RTABU search based optimization approach for trajectory generation [45]. Scherer et al reported an evidence grid with a Laplacian-based potential method for path planning, an obstacle avoidance based on reactive planning, and velocity controller for trajectory generation [47]. In MA, the action space is discretized into action automatons to reduce the search from infinite dimensional space to finite dimensional.…”
Section: Physics-aware Trajectory Planningmentioning
confidence: 99%
“…Suzuki et al used A* based approach for waypoint generation and RTABU search based optimization approach for trajectory generation [45]. Scherer et al reported an evidence grid with a Laplacian-based potential method for path planning, an obstacle avoidance based on reactive planning, and velocity controller for trajectory generation [47]. In MA, the action space is discretized into action automatons to reduce the search from infinite dimensional space to finite dimensional.…”
Section: Physics-aware Trajectory Planningmentioning
confidence: 99%
“…Impressive results for obstacle avoidance on a rotorcraft UAV have been shown by Scherer, Singh, Chamberlain, and Saripalli (2007) and Shim, Chung, Kim, and Sastry (2005). In both cases a scanning laser was used, however, on a Yamaha R-MAX rotorcraft UAV, which is able to lift this type of sensor.…”
Section: Related Workmentioning
confidence: 99%
“…3D laser range scanners are expensive and bulky instruments that are not suitable for small drones. A 3D laser scanner with a limited field of view of 30x40 degrees has been used in [13] on an outdoor helicopter with a payload of 29kg. Mini laser range finders have been used by [14], [15], for detection of large obstacles located directly in front of a drone.…”
Section: Introductionmentioning
confidence: 99%